O estudo do meio nos ginásios vocacionais: análise de fotografias - Albuquerque, Adriana Shiraishi Rollemberg (2015)
The research is to investigate the design and development of the study of the environment in vocational state gyms in São Paulo, in the 1963-1964 period In parallel, seeks to deepen the debate on the historical setting of the study of the environment. Methodologies called study of the environment take into account the contextual nature of educational practice (PONTHUSKA; LOPES, 2010) bringing up the importance of the study of the environment in the structuring and establishment of the curriculum of their own school culture. Resulting from the collection of study photos of the medium provided by the former professor Joseangelo Pompey, who taught between the years 1964-1970, the Vocational College John XXIII American, consolidated the theme and objectives of the research whose intent was to answer the following questions: What were the teaching methodologies and practices developed in American Vocational Gymnasium 1963-1964 ?; As these teaching methodologies and practical dialogue with the Study practices middle ?; What photographs can reveal about the study of the environment in John XXIII Vocation Gym in that period ?. Through the analysis of the sources it was reconstituted a school memory about the study of the environment trying to define the concept for the school and being put on the agenda the idea of a changing curriculum (GOODSON, 1998). Were also used the concepts of school culture, present in Chartier (1990) and Carvalho (1998), in addition to production concepts, cultural appropriation and circulation throughout the work. In conclusion it can say that the images show not only the educational practices Gymnasium as the design of education. The photos helped explain what was done in the study of the environment. The patterns identified contributed to trace a narrative of how it was such work. It was noted that teachers played a key role of "mediators" of relations. Relations between subject and object; and between subject and subject. These appear centrally seeking to conduct the study. Therefore, the analysis of the photographs allow us to observe a crucial point in the history of education, involving the formation and composition of the curriculum, the school and educational thought, the constitution of citizenship and Brazilian citizens in the 60's and 70's, period in which the intervention political and military was remarkable in Brazilian education